First record of deep-sea caridean shrimp Acanthephyra fimbriata Alcock & Anderson, 1894 (Crustacea: Decapoda: Acanthephyridae) from southwest coast of India - Kuberan, G.; Chakraborty, Rekha Devi; Purushothaman, P.; Maheswarudu, G. (Zootaxa, 2018)
The present work reports the new occurrence of deep-sea shrimp Acanthephyra fimbriata Alcock & Anderson, 1894 from southwestern Indian waters. The samples were caught in bottom trawls conducted between the depths of 200 and 350 m from two fish landing centers off Kerala along Arabian Sea from the southwest coast of India during 2015. Additionally, a phylogenetic analysis was used to explore the relationships of the genus Acanthephyra based on two genes: mitochondrial cytochrome c oxidase subunit 1 (COI) and 16S DNA (16S) with the present specimen and sequences retrieved from NCBI GenBank. The results revealed intraspecies (COI: 0–3 % & 16S: 0–0.3 %) and interspecies divergence (COI: 17.5–20.9 % & 16S: 5.2–9.5 %) among A. fimbriata.